Waterbath Temperature Control System with Fuzzy Logic - Levana Forra Wakidi; Annastadia Afifah; Her Gumiwang Ariswati; Dyah Titisari; Shubhrojit Misra (Indonesian Journal of Electronics, Electromedical Engineering, and Medical Informatics, 2023)
Unstable temperature or being outside the control temperature of a sample will cause a change in the quality of the sample itself. The purpose of this study was to create a temperature control system on waterbath with fuzzy logic using 7 labels. Used the DS18B20 sensor as a temperature sensor, a processor in the form of an UNO arduino, a thermostat as part of safety control, and displayed on a 16x4 LCD. Temperature selection between 30°C-60C. Design research using pre-experimental methods with one type group of post-testing design research, by comparing modules with comparison tools in the form of digital thermometers. The results of the research in the manufacture of waterbath tools were conducted compared to the results of measurements in the room with a digital thermometer. Obtained the highest Error value of 0.91% at 35 °C and the lowest error of 0.049% at 60 °C. While the error value based on the setting temperature obtained the highest error value at the temperature setting of 30°C of 1.38% and the lowest error at the temperature setting of 60 °C of 0.05%. The average time required to reach the shortest setting temperature in the temperature range is 27°C-30°C for 193 seconds, and the longest time in the temperature range is 27°C-60°C for 2257 seconds. the results showed that the fuzzy method is better compared to conventional methods. The results of this study can be implemented for waterbath temperature control system to get more stable results in maintaining setting temperature.